The methyltransferase SETD3 regulates mRNA alternative splicing through interacting with hnRNPK - Yue-Yu Kong; Wen-Jie Shu; Shuang Wang; Zhao-Hong Yin; Hongguo Duan; Ke Li; Hai-Ning Du (Cell Insight)
The methyltransferase SETD3 is an enzyme essential for catalyzing histidine-73 methylation on β-Actin, thereby promoting its polymerization and regulating muscle contraction. Although increasing evidence suggests that SETD3 is involved in multiple physiological or pathological events, its biological functions remain incompletely understood. In this study, we utilize in situ proximity labeling combined with mass spectrometry analysis to detect potential interacting partners of SETD3. Unexpectedly, we find that many splicing factors are associated with SETD3. Genome-wide RNA sequencing reveals that SETD3 regulates pre-mRNA splicing events, predominantly influencing exon skipping. Biochemical and bioinformatic analyses suggest that SETD3 interacts with hnRNPK, and they collaboratively regulate exon skipping in a common subset of genes. Functionally, we demonstrate that SETD3 and hnRNPK are required for retention of exon 7 skipping in the FNIP1 gene. This promotes FNIP1-mediated nuclear translocation of the transcription factor TFEB and the subsequent induction of lysosomal and mitochondrial biogenesis. Overall, this study uncovers a novel function of SETD3 in modulating mRNA exon splicing.